Prognostic value of specific KRAS mutations in patients with colorectal peritoneal metastases - Marco Tonello; Dario Baratti; Paolo Sammartino; Andrea Di Giorgio; Manuela Robella; C. Sassaroli; Massimo Framarini; Mario Valle; Antonio Macrì; Luigina Graziosi; Federico Coccolini; Piero Vincenzo Lippolis; et al. (2024)
•The prognostic value of specific KRAS mutations in patients with isolated CRC PM is unclear.•KRAS mutation subgroups can be determined according to specific codon substitution.•KRASMUT1 group has similar prognosis to wild-type patients.•KRASMUT2 patients associated with poorer prognosis than KRASMUT1 and KRASWT.•KRASMUT2 occur in the P-loop region, with decreased GTP hydrolysis, change in polarity and size of AA. BackgroundThere is little evidence on KRAS mutational profiles in colorectal cancer (CRC) peritoneal metastases (PM). This study aims to determine the prevalence of specific KRAS mutations and their prognostic value in a homogeneous cohort of patients with isolated CRC PM treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy.Materials and methodsData were collected from 13 Italian centers, gathered in a collaborative group of the Italian Society of Surgical Oncology. KRAS mutation subtypes have been correlated with clinical and pathological characteristics and survival [overall survival (OS), local (peritoneal) disease-free survival (LDFS) and disease-free survival (DFS)].ResultsKRAS mutations occurred in 172 patients (47.5%) out of the 362 analyzed. Two different prognostic groups of KRAS mutation subtypes were identified: KRASMUT1 (G12R, G13A, G13C, G13V, Q61H, K117N, A146V), median OS > 120 months and KRASMUT2 (G12A, G12C, G12D, G12S, G12V, G13D, A59E, A59V, A146T), OS: 31.2 months. KRASMUT2 mutations mainly occurred in the P-loop region (P < 0.001) with decreased guanosine triphosphate (GTP) hydrolysis activity (P < 0.001) and were more frequently related to size (P < 0.001) and polarity change (P < 0.001) of the substituted amino acid (AA). When KRASMUT1 and KRASMUT2 were combined with other known prognostic factors (peritoneal cancer index, completeness of cytoreduction score, grading, signet ring cell, N status) in multivariate analysis, KRASMUT1 showed a similar survival rate to KRASWT patients, whereas KRASMUT2 was independently associated with poorer prognosis (hazard ratios: OS 2.1, P < 0.001; DFS 1.9, P < 0.001; LDFS 2.5, P < 0.0001).ConclusionsIn patients with CRC PM, different KRAS mutation subgroups can be determined according to specific codon substitution, with some mutations (KRASMUT1) that could have a similar prognosis to wild-type patients. These findings should be further investigated in larger series. There is little evidence on KRAS mutational profiles in colorectal cancer (CRC) peritoneal metastases (PM). This study aims to determine the prevalence of specific KRAS mutations and their prognostic value in a homogeneous cohort of patients with isolated CRC PM treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Data were collected from 13 Italian centers, gathered in a collaborative group of the Italian Society of Surgical Oncology. KRAS mutation subtypes have been correlated with clinical and pathological characteristics and survival [overall survival (OS), local (peritoneal) disease-free survival (LDFS) and disease-free survival (DFS)]. KRAS mutations occurred in 172 patients (47.5%) out of the 362 analyzed. Two different prognostic groups of KRAS mutation subtypes were identified: KRASMUT1 (G12R, G13A, G13C, G13V, Q61H, K117N, A146V), median OS > 120 months and KRASMUT2 (G12A, G12C, G12D, G12S, G12V, G13D, A59E, A59V, A146T), OS: 31.2 months. KRASMUT2 mutations mainly occurred in the P-loop region (P < 0.001) with decreased guanosine triphosphate (GTP) hydrolysis activity (P < 0.001) and were more frequently related to size (P < 0.001) and polarity change (P < 0.001) of the substituted amino acid (AA). When KRASMUT1 and KRASMUT2 were combined with other known prognostic factors (peritoneal cancer index, completeness of cytoreduction score, grading, signet ring cell, N status) in multivariate analysis, KRASMUT1 showed a similar survival rate to KRASWT patients, whereas KRASMUT2 was independently associated with poorer prognosis (hazard ratios: OS 2.1, P < 0.001; DFS 1.9, P < 0.001; LDFS 2.5, P < 0.0001). In patients with CRC PM, different KRAS mutation subgroups can be determined according to specific codon substitution, with some mutations (KRASMUT1) that could have a similar prognosis to wild-type patients. These findings should be further investigated in larger series.